Monitoring system ammonia concentration using fiber optic sensor based surface plasmon resonance - Huda, Erin Ficrah; Harmadi, Harmadi; Muldarisnur, Muldarisnur (Journal of Physics: Theories and Applications, 2023)
A monitoring system for ammonia concentration in waters has been created using fiber optic sensors based on surface plasmon resonance (SPR). Monitoring is carried out to measure the decline in water quality due to the toxic compound ammonia from floating net cages (KJA) activities used as aquaculture sites. The sensor performance was improved by replacing the cladding using gold nanoparticles to increase the sensitivity of the fiber optic sensor based on the SPR phenomenon. The sensor consists of a laser diode as a light source, optical fiber as a waveguide and OPT101 as a photodetector. The Arduino Nano microcontroller is used as a data processor, LoRa as a transmission system and the MCU node as a data receiver. The results of measuring the ammonia concentration received by the MCU node are displayed on a Google spreadsheet in real time. Testing of measuring instruments is carried out by comparing the measurement results with a UV-Vis spectrophotometer. The test results obtained an accuracy value of 94.09% for optical fibers using the dip coating method and 78% for optical fibers using the thermal evaporation coating method.